ANALISA PRODUKTIVITAS DAN EFISIENSI ALAT BERAT PADA PEKERJAAN PENINGKATAN JALAN WAIGETE –GALIT - Stefanus Blawir; Yosef Norbertus Tembu Muda; Alfrendo Satriawan Kabupung (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2023)
In the process of road construction, the use of heavy equipment is very necessary in accelerating the process of carrying out work in accordance with predetermined and planned targets. Machines must be used efficiently, and productivity tool depends on type or type tool, method work, condition work field, as well as time which required for complete something profession. This study uses the actual method of calculating the productivity of heavy equipment, namely the calculation of the speed of the heavy equipment, the efficiency factor of the equipment and the productivity capacity of the heavy equipment used in accordance with what happened in field.The purpose of this final project is to determine the productivity value of heavy equipment in the Waigete - Galit Road Improvement project. Where the productivity value in asphalt pavement layer work is: 1 unit asphalt mixing plant = 16.9 m3/hour, 4 units Hino dump trucks = 3.6 m³/hour, 1 unit asphalt finisher = 18 m3/hour, 1 unit tandem roller = 15.7 m3/hour, 1 unit pneumatic tire roller = 15.9 m³/hour. And calculate the working time required for each heavy equipment based on the number of tools available, namely on asphalt pavement layer work : asphalt mixing plant = 2 days, dumpt truck = 2 days, asphalt finisher = 2 days , tandem roller = 2 days, pneumatic tyred rollers = 2 days.The calculation results obtained are real productivity with a good (good) working efficiency factor in accordance with the real working time in the field.